2021
DOI: 10.5653/cerm.2020.03524
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sesame oil and different doses of estradiol on testicular structure, sperm parameters, and chromatin integrity in old mice

Abstract: Objective: Studies of the effects of estrogens on the male reproductive system have emphasized the role of these hormones in male fertility. Sesame oil has many phytoestrogenic compounds and may improve male fertility. This study investigated the effects of sesame oil and different concentrations of estrogen on sperm parameters and DNA integrity in male mice.Methods: Twenty old NMRI (The Naval Medical Research Institute) male mice (40 weeks; weight, 30–35 g) were treated with sesame oil or different concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…This would be in line with a reduction in sperm DNA fragmentation reported in mice treated with low levels of estradiol (Mohammadzadeh et al, 2021), possibly due to either the antioxidant effect mentioned (Hamden et al, 2008) or due to positive effects on the sperm DNA condensation and packaging (Cacciola et al, 2013). Such a mechanism would corroborate the emerging role of estrogens in the function of germ cells (Correia et al, 2015) and also associations reported between levels of estradiol and decreased sperm DNA fragmentation in two previous human studies (Meeker et al, 2008;Richthoff et al, 2002).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…This would be in line with a reduction in sperm DNA fragmentation reported in mice treated with low levels of estradiol (Mohammadzadeh et al, 2021), possibly due to either the antioxidant effect mentioned (Hamden et al, 2008) or due to positive effects on the sperm DNA condensation and packaging (Cacciola et al, 2013). Such a mechanism would corroborate the emerging role of estrogens in the function of germ cells (Correia et al, 2015) and also associations reported between levels of estradiol and decreased sperm DNA fragmentation in two previous human studies (Meeker et al, 2008;Richthoff et al, 2002).…”
Section: Introductionsupporting
confidence: 81%
“…Since an elevated BMI may be associated with higher estradiol levels (Kahn & Brannigan, 2017 ; MacDonald et al, 2010 ; Vermeulen et al, 2002 ), and since estrogens are reported to play an essential role in the production and maturation of spermatozoa (Carreau & Hess, 2010 ; Dostalova et al, 2017 ) as well as to protect testicular cells against oxidative damage (Hamden et al, 2008 ), we speculated that lower sperm DNA fragmentation in the overweight men (Bandel et al, 2015 ) could be due to higher levels of estradiol. This would be in line with a reduction in sperm DNA fragmentation reported in mice treated with low levels of estradiol (Mohammadzadeh et al, 2021 ), possibly due to either the antioxidant effect mentioned (Hamden et al, 2008 ) or due to positive effects on the sperm DNA condensation and packaging (Cacciola et al, 2013 ). Such a mechanism would corroborate the emerging role of estrogens in the function of germ cells (Correia et al, 2015 ) and also associations reported between levels of estradiol and decreased sperm DNA fragmentation in two previous human studies (Meeker et al, 2008 ; Richthoff et al, 2002 ).…”
Section: Introductionsupporting
confidence: 66%
“…Finally, the three mouse species examined here exhibited 0.4-1.2% positively stained sperm (either completely or partially stained) with chromomycin A3, indicative of defective protamination [61], as opposed to the laboratory mouse, which exhibited values of ~3% [48,57]. In contrast, in other studies, cauda epididymal mouse sperm stained with chromomycin A3 revealed higher values (~10-20% stained) [45][46][47]. The ability of these staining methods to identify alterations in chromatin status is demonstrated by higher percentages of stained mouse sperm under different conditions, such as treatment with estrogens (30%) [46], oxidative stress, age (30-70%) [47], and protamine 1 (90%) or protamine 2 deficiencies (30%) [48].…”
Section: Discussioncontrasting
confidence: 63%
“…In contrast, in other studies, cauda epididymal mouse sperm stained with chromomycin A3 revealed higher values (~10-20% stained) [45][46][47]. The ability of these staining methods to identify alterations in chromatin status is demonstrated by higher percentages of stained mouse sperm under different conditions, such as treatment with estrogens (30%) [46], oxidative stress, age (30-70%) [47], and protamine 1 (90%) or protamine 2 deficiencies (30%) [48]. In comparison to other species, alterations in chromatin status in the mouse are rather low; studies of human, bull, boar, dog, and cat sperm revealed higher proportions of spermatozoa with defects in sperm chromatin compaction [39,42,55,[62][63][64][65].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation